VCBP: A Reliable and Real-Time Group Communication Protocol for Vehicular Ad Hoc Networks - Pereira, Marcela Alves; Sá, Alirio Santos de (Anais do Workshop on Security, Privacy and Reliability on Wireless Sensing Networks (WSENSING); 2022: Anais do II Workshop on Security, Privacy and Reliability on Wireless Sensing Networks, 2022)
Distributed applications for Intelligent Transportation Systems (ITS) based on Vehicular Ad Hoc Networks (VANETs) are prone to constant changes in network topology, disconnections, and message losses. Many distributed applications for ITS require groups of vehicles to coordinate their actions consistently, reliably, and with time constraints – which is a challenge due to the high mobility and (vehicle-to-vehicle) wireless communication of VANETs. In this context, this paper proposes the Vehicular Causal Block Protocol (VCBP) to support the coordination requirements of VANET-based distributed applications for ITS. Our preliminary results show that the VCBP can offer more communication guarantees with a message delivery rate similar to or higher than the other evaluated group communication approaches.